Determination of the Effects of Some Environmental Factors on Raw Milk Somatic Cell Count of Brown Swiss Cows Raised in Farmer Condition - Aziz Şahin; Muzaffer Kaşıkcı (Turkish Journal of Agriculture: Food Science and Technology)
In the current research, it was aimed to determine Somatic Cell Count (SCC) and the factors effecting on SCC in milk samples of Brown Swiss cattle raised at different farm conditions in Yıldızeli district of Sivas province in Turkey. Raw milk samples were collected at morning milking in months of May and November in year 2012. In total, 244 milk samples from 122 Brown Swiss cattle were analyzed. The effects of calving age, farm and test month on SCC were statistically significant. In the present study, the average SCC was determined as 1209696±111361 cells/ml. About 56.6% of milk from November month and about 48.4 % of milk samples from Brown Swiss were containing over 500.000 cell/ ml. As a result, Brown Swiss cattle identified SCC in raw milk samples were significantly higher than the values specified in the legislation of the European Union Commission and Turkish Food Codex.